Diagnosis of Peripheral Lung Lesions by EBUS-Guided TBB in Routine Practice - Ostendorf, U.; Scherff, A.; Khanavkar, B.; Ewig, S.; Hecker, E. (Pneumologie, 2011)
Objective: To determine the diagnostic yield of EBUS guided TBB performed in routine practice with flexible bronchoscopy and under moderate sedation in ambulatory and hospitalized patients.Methods: Bronchoscopy was performed under standard conditions in ambulatory and hospitalised patients. Bronchoscopically invisible peripheral pulmonary lesions were located with 20 MHZ-EBUS-probe and transbronchial biopsy was taken using a guiding sheath. Fluoroscopy was additionally performed as required to identify the lesion.Results: 257 patients with peripheral pulmonal lesions were investigated, with malignancy in 70 % of those with a diagnosis established. 175/257 (68.1 %) of lesions were detected with EBUS. In 139/176 (79.4 %) of these lesions, TBB enabled a final diagnosis. The TBB yield depended on lesion size. It was 61.3 % in lesions ≤ 20 mm, 85.5 % > 20 mm/≤ 30 mm, and 81.2 % in ≥ 30 mm (p < 0.0001). This yield was also affected by the position of the probe (centrally 84.5 %, tangentially 57.6 %, p = 0.01)). Operator experience did not influence the diagnostic yield but considerably shortened investigation time (4.9 ± 3.5 vs. 6.2 ± 4.2 min, p = 0.042). Relevant complications occurred in only 1.9 % (3 cases of postinterventional pneumothorax).Conclusions: In an unselected population, EBUS-guided TBB has a high diagnostic yield in peripheral lesions > 20 mm whereas its yield decreases considerably in smaller lesions. Complications are very rare. EBUS-guided TBB can successfully and safely be performed by flexible bronchoscopy.